Evaluation of physical disabilities in ex-patients with leprosy the time of isolation compulsory - Carvalho, Michele Albuquerque Jales (2013)
Leprosy affects thousands of Brazilians annually presents a significant number of these degrees of physical disability I and II. The aim of this study was to identify the sociodemographic profile and major physical disabilities installed in people who had leprosy at the time of compulsory isolation. This is a descriptive research with quantitative approach, which evaluated 26 residents of a former hospital colony, now called Living Center, located in the town of Maracanaú - EC. A questionnaire was used to define the sociodemographic profile and the Short Form neurological assessment, recommended by WHO to identify the degree of disability. Data were collected and stored in an Excel spreadsheet software. After this step the database was imported and processed by the EPI-INFO (version 6) program. There was a predominance of males (57.7%), incomplete primary education (50.0%), the age ranged between 40-80 years with income below the poverty level, as marital status, (38.5%) and were married (30.8%) were widowed. The majority (88.5%) presented grade II disability. The most affected sectors were the feet and hands indicating a loss of sensation in the lower limbs (50.0%) and higher (38.46%) in most evaluated. It is concluded that the main disability present in people affected by leprosy are due to secondary injuries mainly due to the loss of sensitivity, as well as the insufficiency or absence of prevention and physical rehabilitation.